Consumer Perception Toward Store Image Of Bandung Traditional Market - Yulinda Pancawuri; Raden R Rahadi; Fajar S. A Prabowo (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2018)
This research aims to find out what factors that affect consumer perceptions of store image Traditional Markets in Bandung. The sample in this research is 400 people who live in Bandung are calculated based on sampling convenience sampling. The method used is factors analysis. Consumer perceptions of store image measured through the dissemination of a questionnaire with items 19 statement. The results of factors analysis obtained 5 factors that affect consumer perceptions, these factors include in-store & location convenience and store atmosphere (4,781), convenience and merchandising (1,986), price (1,588), public facilities (1,079), quality of merchandising (1,005).